Corporate Social Responsibility Performance in the Environmental Sector: Role of Board Directors and Foreign Ownership - Safitri, Devi; Anisma, Yuneita; Yusralaini, Yusralaini; Zarefar, Arumega (Accounting Analysis Journal, 2025)
Purpose: The purpose of this research is to examine and experimentally demonstrate how foreign ownership and director qualities affect CSR performance, particularly in the environmental sector. The presence of independent directors, board size, and gender diversity serve as markers of the qualities of the board.  The variables controlled in this study include company size, ROA, ROE, DER, and industry sensitivity. Method: The study utilizes a sample of 256 companies that are involved in PROPER on the IDX, except for finance. The data analysis technique used is Ordinary Least Squares (OLS) using STATA 17. Findings: The Research results show that only board size can improve CSR performance in the environmental field. Meanwhile, gender diversity on the board, independent directors, and foreign ownership do not influence the success of CSR in the environmental field. Novelty: The study differs from previous research by focusing specifically on corporate social responsibility performance in the environmental sector. To make sure the data used to assess CSR performance in the environmental sphere is objective and quantifiable, the researcher utilises the PROPER score that the firm received from the Ministry of Environment and Forestry.